Macroeconomic planning and the needs of the small business sector - Thomas, Clive Y. (Univ. of Guyana. Institute of Development Studies GeorgetownGY, 1993)
Highlights the reasons why small business enterprise activity should be placed within a macroeconomic context, with particular reference to Guyana.